Transvenous Approach for the Treatment of cerebral Arteriovenous Malformations (TATAM): Study protocol of a randomised controlled trial. Issue 3 (June 2019) - Fahed, Robert; Darsaut, Tim E; Mounayer, Charbel; Chapot, René; Piotin, Michel; Blanc, Raphaël; Mendes Pereira, Vitor; Abud, Daniel G; Iancu, Dana; Weill, Alain; Roy, Daniel; Nico, Lorena; et al.
Background: Transvenous embolisation is a promising technique but the benefits remain uncertain. We hypothesised that transvenous embolisation leads to a higher rate of arteriovenous malformation angiographic occlusion than transarterial embolisation. Methods: The Transvenous Approach for the Treatment of cerebral Arteriovenous Malformations (TATAM) is an investigator initiated, multicentre, prospective, phase 2, randomised controlled clinical trial. To test the hypothesis that transvenous embolisation is superior to transarterial embolisation for arteriovenous malformation obliteration, 76 patients with arteriovenous malformations considered curable by up to two sessions of endovascular therapy will be randomly allocated 1:1 to treatment with either transvenous embolisation (with or without transarterial embolisation) (experimental arm) or transarterial embolisation alone (control arm). The primary endpoint of the trial is complete arteriovenous malformation occlusion, assessed by catheter cerebral angiography. Complete occlusions will be confirmed at 3 months, while incompletely occluded arteriovenous malformations, considered treatment failures, will then be eligible for complementary treatments by surgery, radiation therapy, or even transvenous embolisation. Standard procedural safety outcomes will also be assessed. Patient selection will be validated by a case selection committee, and participating centres with limited experience in transvenous embolisation will be proctored. Discussion: The TATAM trial is a transparent research framework designed to offer a promising but still unvalidated treatment to selected arteriovenous malformation patients. Clinical Trial Registration-URL: http://www.clinicaltrials.gov . Unique identifier: NCT03691870.